PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PHAIR-SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II SD NEGERI 59 PEKANBARU - Poppy Pebrikasari; Syahrilfuddin '; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the low value of IPA. Preliminary data result of learning students of class II of SD Negeri 59 Pekanbaru is from the 34 students, only 16 peoples or 47,06% completed or reached the KKM and 18 peoples or 52,94% were not completed. Based on these problems, it is necessary given way to solve the problem include applying model cooperative type Think-Pair-Share (TPS). Cooperative type Think-Pair-Share (TPS) presents the learning material to provide opportunities for students to work alone as well as in collaboration with friends, so that they can easily understand the material presented teachers. Subjects in this research were students of class II of SD Negeri 59 Pekanbaru. This research was conducted in two cycles, by doing the daily test of the end of each cycle. Based on the research of student learning outcomes increased visits from the basic score 67,06 to 75,88 in the first cycle with percentage increase 13,15% from the base score, cycle II, the average value of 81,76 with a percentage increase 21,92%. The result of this research shows that the cooperative type Think-Pair-Share (TPS) model can increase IPA studies, completeness IPA learning outcomes in first cycle is 64,71%, in second cycle increased to 85,29%.Keywords: Cooperative Type Think-Pair-Share (TPS), IPA Learning Outcomes.